Two Misconstruals of Frege's Theory of Colouring. (24th November 2018) - Sander, Thorsten
ABSTRACT: Many scholars claim that Frege's theory of colouring (Färbung) is committed to a radical form of subjectivism or emotivism. Some other scholars claim that Frege's concept of colouring is a precursor to Grice's notion of conventional implicature. I argue that both of these claims are mistaken. Finally, I propose a taxonomy of Fregean colourings: for Frege, there are (1) purely aesthetic colourings, (2) communicative colourings or hints, (3) non-communicative colourings.